Innovative Deep Learning–Driven Indonesian Language Instruction: Development and Effectiveness in Improving Elementary Reading Literacy - Ni Ketut Desia Tristiantari; Dani Gunawan; Decenni Amelia; Ni Wayan Monik Rismadewi; Komang Sujendra Diputra; Gusti Ayu Putu Sukma Trisna (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to develop an innovative Indonesian language learning design based on a deep learning approach and to evaluate its effectiveness in improving elementary school students' reading literacy. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research participants included two content experts, two instructional design experts, and 65 elementary school students. Data were collected through validation questionnaires to assess product feasibility and multiple-choice tests to measure students’ reading literacy skills. The data were analyzed using descriptive quantitative techniques and the normalized gain (N-Gain) test. The results revealed that: (1) students’ initial reading literacy achievement, as measured by the pre-test, was categorized as moderate, with a mean score of 63.61; (2) the developed learning design was rated as highly feasible by expert validators, achieving an average score of 4.63 out of 5.00; (3) students’ post-test performance improved substantially, reaching a mean score of 84.54 and falling within the very high category; and (4) the N-Gain value was 0.58, indicating a moderate level of improvement. These findings indicate that the deep learning-based Indonesian language learning design is effective in enhancing elementary school students’ reading literacy. This study highlights the potential of integrating cognitive and affective dimensions through a deep learning approach to foster a more meaningful learning environment. Such an approach enables students not only to comprehend texts but also to critically analyze, evaluate, and reflect on information. Therefore, the proposed learning design may serve as a valuable reference for educators seeking to transform literacy instruction into a more student-centered and meaningful learning experience at the elementary school level.